2020
DOI: 10.2147/opth.s274567
|View full text |Cite
|
Sign up to set email alerts
|

<p>Review of Ocular Injuries in Patients with Orbital Wall Fractures: A 5-Year Retrospective Analysis</p>

Abstract: a level-one trauma center, to help determine the most appropriate setting for the initial dilated fundus examination by ophthalmologists. Methods: A retrospective study was performed from January 2008 to January 2013 of patients diagnosed with orbital wall fracture secondary to trauma. Exclusion criteria included unknown mechanism of injury, the absence of ophthalmology consultation, or absence of imaging. Data collected included age, gender, mechanism of injury, visual acuity, and anterior/ posterior segment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 21 publications
7
21
0
Order By: Relevance
“…This is in contrast to other studies showing orbital roof fractures occurring in men 89% to 93% of the time and usually caused by high-energy impact injuries. 8 This could be due in part to a smaller sample size presenting with orbital roof fractures; however, the fractures being caused by high energy impact injuries are consistent with our study which showed that superior wall orbital fractures were more frequently caused by forms of direct impact and MVCs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is in contrast to other studies showing orbital roof fractures occurring in men 89% to 93% of the time and usually caused by high-energy impact injuries. 8 This could be due in part to a smaller sample size presenting with orbital roof fractures; however, the fractures being caused by high energy impact injuries are consistent with our study which showed that superior wall orbital fractures were more frequently caused by forms of direct impact and MVCs.…”
Section: Discussionsupporting
confidence: 90%
“…Our data follows the literature that a very small percentage of orbit fractures require surgical correction 8,28. Open reduction and internal fixation was the procedure of choice to repair all orbital fractures and was by far the most commonly utilized procedure in our study representing 57.9% (44/76) of the surgical interventions that were done.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Conservative treatment is often used for small orbital fractures without displacement ( 7 ), while, for large displaced fractures, surgical intervention is necessary ( 8 , 9 ). Orbital fractures may cause exophthalmos ( 10 ), enophthalmos ( 11 ), diplopia ( 12 ), entropion ( 13 ), subconjunctival hemorrhage ( 14 ), and even blindness ( 15 ). Therefore, early monitoring and termination of adverse disease progression in patients with OF are very important.…”
Section: Introductionmentioning
confidence: 99%
“…Conservative treatment is often used for small orbital fractures without displacement [7], while for large displaced fractures surgical intervention is necessary [8,9]. Orbital fractures may cause exophthalmos [10], enophthalmos [11], diplopia [12], entropion [13], subconjunctival hemorrhage [14] and even blindness [15]. Therefore, early monitoring and termination of adverse disease progression in patients with OF is very important.The use of modern imaging technology to study the brain activity of patients with OF may be important as a means by which to improve understanding of the mechanism of potential pathological changes in this condition, and may therefore be bene cial to the management of complications.…”
Section: Introductionmentioning
confidence: 99%